Housing characteristics and changes across waves - Maguire, Brigit; Edwards, Ben; Soloff, Carol (AIFS, 2012)
The characteristics of children’s homes and family living arrangements, being a large part of their physical and social environment, have important influences on their development and wellbeing (Bronfenbrenner & Morris, 2006). A recent scoping study (Dockery et al., 2010) identified Growing Up in Australia: The Longitudinal Study of Australian Children (LSAC) as a useful source of data for analysing housing and child developmental outcomes. This chapter describes three aspects of housing that are expected to be important for children’s outcomes: housing mobility, tenure and overcrowding (Dockery et al., 2010).
Australian Institute of Family Studies, LSAC Annual Statistical Report 2011
Keywords: Children -- Outcomes; Housing -- Type; Child Development; Housing -- Moving; Health -- Wellbeing; Childhood and child development; Health and wellbeing; Child Development; Health; Children; Housing; Outcomes; Wellbeing; Type; Moving; Childhood and child development; Health and wellbeing